Edukasi penggunaan internet sehat untuk mengenali berita Hoax bagi pemuda Dusun Pepe Desa Pajaran Kab. Madiun - S Saifulloh; Sri Anardani; Qoirrudin Raga Pratama (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2022)
The population using the internet is currently dominated by teenagers to children with in fact its use as online games and access to social media both as a means of communication and as a means of finding information. Internet penetration in people's lives has a positive impact, including using the internet as a social media-based communication facility, accessing public services, being used as a means of marketing MSME products and banking transactions. In addition to the many positive things that can be felt, there are also many crimes that arise from internet use for internet users. Internet access for users often ignores access restrictions or has not been wise in its use, such as people uploading personal things (KTP) as posts, unconsciously using the phrase SARA in communicating to accessing pornographic sites so that the author sees a problem with the object of research, namely the Pepe hamlet community. Pajajaran Village, Madiun Regency, to provide healthy internet education assistance to recognize Hoax news as a discussion study of this problem using a risk management approach with a SWOT analysis that is more directed to the use of technology.